Study of a dynamic substitution box (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
The paper examines a previously developed method for generating a dynamic substitutionbox. This method allows generating substitution boxes (S-boxes) that change depending on the values ​​of some parameter obtained from the secret key of the algorithm. The generated S-boxes are resistant to linear and differential cryptanalysis, since they are random, not known in advance, and depend on the secret key. The obtained dynamic substitution boxes were examined for nonlinearity, and the results were compared with S-boxes of well-known symmetric block algorithms such as AES, Kuznyechik, SM4, BelT, and Kalyna.
Keywords: encryption algorithm, substitution box, dynamic S-box, nonlinear transformation